Pengaruh Kualitas Produk dan Harga Terhadap Minat Beli Ulang (Studi Pada Aka Coffee Dau Malang) - Yusril Amar Qotafi; Budi Wahono; Ratna Tri Hardaningtyas (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This research was conducted to determine the effect of product quality and price on repurchase intention (Study on Aka Coffee Dau Malang). This research belongs to the type of explanatory research with a quantitative approach, which was conducted to examine the effect between variables. The population in this study were customers aka coffee in the city of Malang. From this population a sample will be determined using the formula method from Malhotra so that a sample of 60 samples is obtained. Data analysis in this study consisted of instrument testing, classical assumption test, multiple linear regression analysis, hypothesis testing, and coefficient of determination test. The results of this study indicate that based on the results of the t test and f test there is a simultaneous influence between the effect of product quality and price on repurchase intention (Study on Aka Coffee Dau Malang). Adjusted R Square of 57.2% to the dependent variable, namely repurchase interest can be explained by the product quality variable (X1), price quality (X2), while 42.8% is explained by other variables outside the research model. Keyword: Product Quality, Price, Repurchase Interest